The genocidal violence in Burundi : an analysis of 1993 conflict - Saidi, Mpawenimana Abdallah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
This study examines the genocidal violence in Burundi focusing on the 1993. It carries out an investigation into the conflicts to reveal the real causes and discuss changes in Hutu-Tutsi relations as a result of political transformation between 1960 and 2006. In studying the causes of conflict, the study considers the following important determinants such as Economic, Political, Ethnicity, and Geography. The study points out that in order to reduce the likelihood of conflicts in Burundi, it is essential to promote inclusive development and reduce the inequalities between groups. This study is analytical and qualitative and uses both Primary and Secondary sources of data collection. The study found that the conflict was caused by a combination of ethnic, political, economic and geographical factors with ethnicity as the main cause. To sustain peace and experience true development, the study suggests that Burundians should be invited to define, understand, and exchange ideas concerning the importance of "democracy". The study suggests that the Arusha agreements signed by various Burundian parties involved in conflict should be fully implemented and respected for durable peace to take place.